Method for selectively degrading resistance genes in water body through electrochemical oxidation
A glassy carbon electrode loaded with carbon nanotubes and ethylene end groups, combined with molecular imprinting, effectively addresses the challenge of selectively degrading antibiotic resistance genes in water through electrochemical oxidation, ensuring high selectivity and stability.
Patent Information
- Application Number
- CN202411400638.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Current water treatment processes are ineffective in selectively removing antibiotic resistance genes (ARGs) and are easily affected by other chemical pollutants, posing a threat to public health.
A method using a glassy carbon electrode loaded with carbon nanotubes, modified with ethylene end groups and molecular imprinting, coupled with electrochemical oxidation to selectively degrade ARGs by recognizing and binding to these genes.
The method achieves efficient and selective removal of ARGs, maintaining recognition performance over multiple uses and enhancing electrochemical activity, while minimizing the detachment of molecular imprinting.
Smart Images

Figure CN119143250A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water pollutant degradation, and in particular to a method for selectively degrading resistance genes in water by electrochemical oxidation. Background Art
[0002] Excessive or improper use of antibiotics induces pathogenic bacteria to produce antibiotic resistance genes (ARGs), which can continuously spread resistance through horizontal gene transfer (HGT), posing a serious threat to public health and are considered a new type of environmental pollutant. In 2019, 4.95 million deaths worldwide were related to bacterial resistance. Current water treatment processes are not effective in removing resistance genes.
[0003] In the prior art, treatment methods including electrochemical oxidation are not selective for the removal of resistance genes and are easily affected by other chemical pollutants, resulting in non-selective removal of ARGs. Therefore, it is necessary to improve the selective removal of resistance genes. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for selectively degrading resistance genes in water by electrochemical oxidation.
[0005] In a first aspect, the present invention provides a method for selectively degrading resistance genes in water by electrochemical oxidation, comprising:
[0006] Using the first electrode as an anode and the second electrode as a cathode, applying current to degrade the resistance gene in the water body;
[0007] Wherein, the first electrode is a glassy carbon electrode loaded with molecular imprinting;
[0008] The molecularly imprinted glassy carbon electrode is obtained by loading the glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and loading the molecular imprints. The molecular imprints are used to selectively identify resistance genes from chemical pollutants in water and combine with the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria.
[0009] Description: Through the above method, the glassy carbon electrode is used as the anode and the second electrode as the cathode, and current is applied to degrade the resistance genes in the water. Molecular imprinting technology is coupled with electrochemical oxidation to prepare a glassy carbon electrode loaded with DNA molecular imprinting. The glassy carbon electrode can specifically recognize and bind to the target resistance gene in the electrochemical reaction and degrade it through the electrochemical oxidation process. This method combines the high selectivity of molecular imprinting and the strong oxidizing ability of electrochemical oxidation to achieve efficient and selective removal of resistance genes in water.
[0010] Furthermore, the method of loading the glassy carbon electrode with carbon nanotubes comprises:
[0011] The glassy carbon electrode is placed in a carboxylated carbon nanotube dispersion, and deposited at a set voltage of -1 to -1.2 V for a deposition time of 1000 to 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode;
[0012] The carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent, and the concentration of the carboxylated carbon nanotube dispersion is 0.02-0.05 mg / mL.
[0013] Note: By loading carbon nanotubes on the glassy carbon electrode, the electrochemical activity, electron transfer and mechanical stability can be enhanced. At the same time, the loading stability of molecular imprinting can be enhanced, so that the corresponding recognition performance can be maintained during multiple uses and long-term operation.
[0014] Further, the method for modifying the ethylene end groups comprises:
[0015] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50-70° C. for 20-30 hours to obtain a precipitate;
[0016] S1-2, after washing and drying the precipitate, adding it to tetrahydrofuran, adding 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 40-60° C. for 20-30 h, and then centrifuging, washing, and drying to obtain a glassy carbon electrode modified with ethylene end groups;
[0017] Among them, the addition ratio of glassy carbon electrode, tetrahydrofuran, dichlorothionyl in S1-1 and tetrahydrofuran, 3-butene-1-ol, 4-dimethylaminopyridine in S1-2 is: 10-30g: 300-500ml; 10-20ml: 300-500ml: 10-30ml: 10-30ml.
[0018] Description: By modifying the glassy carbon electrode with ethylene end groups, the electrochemical activity of the electrode surface can be improved, and the selective recognition ability of the electrode for specific analytes can be improved through the specific interaction between the ethylene end groups and other molecules. The above-mentioned combination is more preferred, and the degradation resistance gene of the obtained glassy carbon electrode has a better effect.
[0019] Furthermore, the second electrode is any one of a platinum electrode, a titanium electrode, a glassy carbon electrode, a BDD electrode and a metal oxide electrode.
[0020] Furthermore, the method for loading molecular imprinting on the glassy carbon electrode comprises:
[0021] S1. Put the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes and then add the crosslinking agent and initiator;
[0022] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0023] Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linking agent, and initiator are as follows: 10-30 g of glassy carbon electrode after ethylene end group modification, 200-300 mL of acetonitrile, 100-200 mL of toluene, 10 mmol of template molecule guanine, 1-5 mol of functional monomer methacrylic acid, 100-200 mg of cross-linking agent, and 10-40 mg of initiator.
[0024] Note: Through the above molecular imprinting loading method, the stability of molecular imprinting loading can be further enhanced through loading conditions, solving the problem of easy detachment of molecular imprinting.
[0025] Furthermore, the molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm.
[0026] Furthermore, the current density of the applied current is: 50-60 mA / cm 2 , the degradation time is 10 to 40 minutes.
[0027] Note: The above current density is more preferred and has a better effect on degrading resistance genes.
[0028] Furthermore, the chemical pollutants are humic acid and its derivatives, glucose and its derivatives, amino acids and their derivatives.
[0029] Furthermore, the antibiotic resistance genes include: tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes and lactam resistance genes.
[0030] The beneficial effects of the present invention are:
[0031] The present invention combines molecular imprinting technology with electrochemical degradation, and can utilize the strong oxidizing effect of the electrochemical degradation process, combined with the selective function of molecular imprinting technology on resistance genes, to achieve efficient degradation of resistance genes in water bodies; at the same time, since the glassy carbon material electrode has the problem of molecular imprinting load falling off from the electrode surface during the electrochemical reaction process, the present invention can form a better structure on the surface of the glassy carbon electrode by loading the glassy carbon electrode with carbon nanotubes and modifying the ethylene end groups, thereby solving the problem of easy falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the principle of molecular imprinting technology of the present invention;
[0033] Figure 2 is a standard curve diagram of qPCR quantitative detection of resistance genes in the experimental example of the present invention;
[0034] Figure 3 It is a degradation efficiency diagram of different ratios of guanine molecules and functional monomer methacrylic acid of the present invention;
[0035] Figure 4 is the SEM image of the glassy carbon electrode of Example 1 of the present invention and Comparative Example 2;
[0036] Figure 5 This is a graph showing the elemental analysis results of the molecularly imprinted glassy carbon electrode by XPS in Example 1 of the present invention;
[0037] Figure 6 is the C1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0038] Figure 7 is the O1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0039] Figure 8 is the N1s narrow spectrum of the glassy carbon electrode of Example 1 of the present invention;
[0040] Fig. 9 is a comparison diagram of the degradation effects of Example 1 and Comparative Example 2 on resistance genes of Example 1 of the present invention;
[0041] Fig.10 is a graph showing the removal rate of resistance genes at different current densities in Example 1 of the present invention;
[0042] Fig.11 is a graph showing the removal rate of extracellular resistance genes at different electrolyte concentrations in Example 1 of the present invention;
[0043] Fig.12 is the removal efficiency of the extracellular resistance gene under the two-component system of Example 1 of the present invention;
[0044] Fig.13 This is the kinetic curve of electrochemical oxidation degradation of extracellular resistance genes in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0046] like Figure 1As shown in the figure, molecular imprinting technology can achieve specific recognition and binding of target molecules by creating cavities in the polymer matrix that match the shape and functional groups of the template molecules. In this process, the template molecules are first mixed with monomers, and then a polymerization reaction is initiated to form a polymer containing the template molecules. Afterwards, the template molecules are removed from the polymer, leaving cavities that are complementary to the shape and functional groups of the template molecules. These cavities can specifically recognize and bind to the same template molecules, thereby achieving selective capture of target molecules.
[0047] Example 1: A method for selectively degrading resistance genes in water by electrochemical oxidation, comprising: using a first electrode as an anode and a second electrode as a cathode, applying current to degrade resistance genes in water;
[0048] Wherein, the first electrode is a glassy carbon electrode loaded with molecular imprinting;
[0049] The glassy carbon electrode loaded with molecular imprinting is obtained by loading the glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and loading the molecular imprinting. The molecular imprinting is used to selectively identify resistance genes from chemical pollutants in water and bind to the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria, and the second electrode is a platinum electrode. The antibiotic resistance genes include tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes, and lactam resistance genes.
[0050] The method for loading the glassy carbon electrode with carbon nanotubes comprises:
[0051] The glassy carbon electrode was polished with metallographic sandpaper, and then polished to a mirror surface with 1.0um, 0.3um and 0.05um Al2O3 polishing powder on suede, and then cleaned with acetone solution and water ultrasonic cleaning.
[0052] The electrode was placed in a deoxygenated 0.03 mg / mL carboxylated carbon nanotube dispersion, the deposition voltage was -1.2 V, the deposition time was 1200 s, and the supporting electrolyte was 0.1 mol / L lithium perchlorate, to obtain a carbon nanotube-loaded glassy carbon electrode;
[0053] Wherein, the carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent;
[0054] The methods for the modification of the ethylene end groups include:
[0055] S1-1, adding a glassy carbon electrode loaded with carbon nanotubes to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 60° C. for 24 hours to obtain a precipitate;
[0056] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 50° C. for 24 hours, and then centrifuge, wash and dry to obtain a glassy carbon electrode modified with ethylene end groups.
[0057] The addition ratio of the glassy carbon electrode, thionyl chloride and tetrahydrofuran in S1-1 is: 20 g: 15 ml: 400 ml;
[0058] The addition ratio of tetrahydrofuran, 3-butene-1-ol and 4-dimethylaminopyridine in S1-2 is: 400ml:20ml:20ml.
[0059] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0060] S1. Put the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; after stirring for 30 minutes, add the crosslinker and initiator (the crosslinker is ethylene glycol dimethacrylate and the initiator is 2,2'-azobisisobutyronitrile);
[0061] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0062] Among them, the added amounts of glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linking agent, and initiator are: 15 g of glassy carbon electrode after ethylene end group modification, 250 mL of acetonitrile, 150 mL of toluene, 10 mmol of template molecule guanine, 3 mol of functional monomer methacrylic acid, 150 mg of cross-linking agent, and 20 mg of initiator.
[0063] The molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm. The current density of the applied current is: 53.08 mA / cm 2 .
[0064] Example 2: The difference between this example and Example 1 is that the second electrode is a titanium electrode; the method for loading the glassy carbon electrode with carbon nanotubes includes: placing the glassy carbon electrode in a 0.02 mg / mL carboxylated carbon nanotube dispersion, setting the voltage to -1 V for deposition, and the deposition time to 1000 s to obtain a carbon nanotube-loaded glassy carbon electrode.
[0065] The methods for the modification of the ethylene end groups include:
[0066] S1-1, adding a glassy carbon electrode loaded with carbon nanotubes to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50° C. for 20 h to obtain a precipitate;
[0067] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 60° C. for 20 h, and then centrifuge, wash and dry to obtain a glassy carbon electrode modified with ethylene end groups.
[0068] The addition ratio of the glassy carbon electrode, thionyl chloride and tetrahydrofuran in S1-1 is: 10 g: 10 ml: 300 ml;
[0069] The addition ratio of tetrahydrofuran, 3-butene-1-ol and 4-dimethylaminopyridine in S1-2 is: 500ml:30ml:30ml.
[0070] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0071] S1. Put the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes and then add the crosslinking agent and initiator;
[0072] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0073] Among them, the added amounts of glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linking agent, and initiator are: 30 g of glassy carbon electrode after ethylene end group modification, 300 mL of acetonitrile, 100 mL of toluene, 10 mmol of template molecule guanine, 5 mol of functional monomer methacrylic acid, 200 mg of cross-linking agent, and 40 mg of initiator.
[0074] The current density of the applied current is: 60 mA / cm 2 .
[0075] Embodiment 3: The second electrode is a glassy carbon electrode;
[0076] The method for loading the glassy carbon electrode with carbon nanotubes comprises:
[0077] The glassy carbon electrode was placed in a 0.05 mg / mL carboxylated carbon nanotube dispersion, the voltage was set to -1.2 V for deposition, and the deposition time was 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode.
[0078] The methods for the modification of the ethylene end groups include:
[0079] S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 70° C. for 30 h to obtain a precipitate;
[0080] S1-2. After washing and drying the precipitate, add it to tetrahydrofuran, add 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 40° C. for 30 hours, and then centrifuge, wash and dry to obtain a glassy carbon electrode modified with ethylene end groups.
[0081] The addition ratio of the glassy carbon electrode, thionyl chloride and tetrahydrofuran in S1-1 is: 30 g: 20 ml: 500 ml;
[0082] The addition ratio of tetrahydrofuran, 3-butene-1-ol and 4-dimethylaminopyridine in S1-2 is: 300ml:10ml:30ml.
[0083] The method for loading molecular imprinting on a glassy carbon electrode comprises:
[0084] S1. Put the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes and then add the crosslinking agent and initiator;
[0085] S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode;
[0086] Among them, the added amounts of glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linking agent, and initiator are: 10g glassy carbon electrode after ethylene end group modification, 200mL acetonitrile, 200mL toluene, 10mmol template molecule guanine, 1mol functional monomer methacrylic acid, 100mg cross-linking agent, and 10mg initiator.
[0087] The current density of the applied current is: 50mA / cm 2 .
[0088] Comparative Example 1: The glassy carbon electrode was not subjected to carbon nanotube loading, ethylene end group modification, or guanine imprinting loading;
[0089] Comparative Example 2: Only carbon nanotube loading and ethylene end group modification were performed on the glassy carbon electrode, and guanine molecular imprinting loading was not performed;
[0090] Comparative Example 3: Only carbon nanotubes were loaded on the glassy carbon electrode without ethylene end group modification or guanine molecular imprinting loading;
[0091] Comparative Example 4: Only guanine molecular imprinting loading was performed on the glassy carbon electrode, and no carbon nanotube loading and ethylene end group modification were performed.
[0092] Experimental example:
[0093] 1. Degradation effect example
[0094] Take the following resistance gene NDM-1 as an example for degradation:
[0095] The acquisition process of the resistance gene NDM-1 is as follows:
[0096] Cultivation of NDM-1 and extraction of plasmid
[0097] LB medium was prepared (each 100 mL of medium contained: 1.0 g of sodium chloride, 0.5 g of yeast powder, 1.0 g of peptone, and the pH was adjusted to 7.0-7.2 using 40 g / L sodium hydroxide solution), NDM-1 bacterial solution and kanamycin sulfate were added (500 μL of 30 mg / mL kanamycin sulfate and 100 mL of NDM-1 bacterial solution were added to each 100 mL of LB), and cultured overnight in an air bath shaker at 37°C; plasmid extraction was performed according to the DP105 rapid plasmid extraction kit (TIANGEN), and the extracted plasmid was stored in a -21°C refrigerator for later use.
[0098] Molecularly imprinted glassy carbon electrodes specifically degrade extracellular resistance genes
[0099] The degradation reaction was carried out in a beaker, and a cover was made of a foam plastic board to ensure that the electrode spacing was 2 cm. A glassy carbon electrode loaded with molecular imprinting (or a glassy carbon electrode without guanine molecular imprinting in comparative example 2) was fixed with an electrode clamp as an anode, a platinum electrode as a cathode, sodium sulfate as an electrolyte, and a DC power supply. The plasmid used was obtained by diluting the plasmid stock solution 500 times. A certain amount of solution in the system was taken out at regular intervals (two parallel samples were taken each time), and the qPCR detection system was configured after diluting it 1000 times with a 50 mL colorimetric tube, and then the measurement was performed using qPCR.
[0100] qPCR quantitative detection of resistance genes
[0101] The standard curve (CT value and logarithm of ARG absolute abundance) was obtained by serially diluting the plasmid 10 times. The reaction system was configured using a fluorescence quantitative kit (TIANGEN), and the NDM-1 forward primer (5'
[0102] The composition of the system is shown in Table 1. The reaction conditions are 95°C pre-denaturation for 30 s, 95°C denaturation for 10 s, 60°C annealing for 20 s, 95°C extension for 15 s, and 40 cycles in total.
[0103] Table 1 qPCR reaction system composition
[0104] System composition Dose (μL) TOR 10 NDM-1 forward primer 0.8 NDM-1 reverse primer 0.8 Sterile water 6.4 Samples to be tested 2
[0105] The qPCR standard curve is obtained by diluting the DNA stock solution in a 10-fold gradient, sampling and detecting the CT value by qPCR, and plotting the curve of lgCDNA and CT value. The experimental results are shown in Table 2. The standard curve obtained by fitting the table data is as follows Figure 2 .
[0106] Table 2 qPCR standard curve results
[0107]
[0108] According to the fitting results, lgCDNA=-0.25548CT+19.27699, R2=0.98195, and the calculation formula of DNA copy value can be obtained by transformation, as shown in the following formula (1):
[0109] C DNA =10 -0.25548CT+19.27699 (1)
[0110] The results of subsequent experiments were transformed using this formula.
[0111] The degradation rate was calculated according to formula (2), where c0 represents the initial DNA copy number, c represents the DNA copy number at a specific moment, and the units are copies / mL.
[0112]
[0113] Experimental results:
[0114] 1. Characterization:
[0115] Characterization and Analysis of Molecularly Imprinted Glassy Carbon Electrode
[0116] Guanine: MAA (functional monomer methacrylic acid) = 1:5, 2:5, 1:2 and 1:1 (molar ratio), respectively, at a current density of 53.08 mA / cm 2The electrolyte concentration was 0.2M Na2SO4 at room temperature to degrade the extracellular resistance gene. Samples were taken for testing at 0min, 10min, 20min and 30min. The removal rate-time curve was calculated based on the experimental results. Figure 3 By comparing the degradation effects of these four electrodes, the optimal preparation conditions were obtained. Figure 3 From the comparison, it can be seen that the degradation effects of the glassy carbon electrodes loaded with molecular imprinting of different ratios on the extracellular resistance genes are relatively similar. The degradation rate of the glassy carbon electrode loaded with molecular imprinting (1:1) is relatively slow. The degradation effects of the glassy carbon electrode loaded with molecular imprinting (1:5) and the glassy carbon electrode loaded with molecular imprinting (1:1) are relatively close, but the degradation rate of the former decreases faster after 20 minutes. The glassy carbon electrode loaded with molecular imprinting (1:2) has the highest removal rate of resistance genes at 30 minutes, and it always maintains a relatively fast rate during the reaction. Based on the above analysis, the glassy carbon electrode loaded with molecular imprinting prepared at a ratio of guanine to MAA of 1:2 has the best oxidative removal effect on extracellular resistance genes. The glassy carbon electrodes loaded with molecular imprinting mentioned below in this chapter refer to the glassy carbon electrodes loaded with molecular imprinting (1:2).
[0117] Morphological analysis of molecularly imprinted glassy carbon electrodes
[0118] The surface morphology of the glassy carbon electrode loaded with molecular imprinting and the glassy carbon electrode without guanine molecular imprinting loading in comparative example 2 was observed by scanning electron microscopy, as follows Figure 4 , which are the morphologies of the glassy carbon electrode loaded with molecular imprinting and the glassy carbon electrode without guanine molecular imprinting in comparative example 2 at different magnifications. When the average particle size is 1 μm, the surface of the glassy carbon electrode loaded with molecular imprinting (c) shows a very rough state, with many protrusions and depressions, while the surface of the glassy carbon electrode without guanine molecular imprinting in comparative example 2 (d) is relatively flat, without too many protrusions and depressions, and shows a block-like staggered distribution. When the average particle size is 100 nm, the surface of the glassy carbon electrode loaded with molecular imprinting (a) shows a larger concave part, similar to a channel, while the surface of the glassy carbon electrode without guanine molecular imprinting in comparative example 2 (b) is relatively full and has no structure similar to a hole. Through comprehensive analysis of the surface morphology and the structure of the molecularly imprinted glassy carbon electrode, guanine was added as a template molecule during the preparation of the molecularly imprinted glassy carbon electrode, and then the guanine in the polymer was washed away by hydrochloric acid, leaving a specific imprint of guanine, which should leave multiple guanine-imprinted holes on the surface of the electrode material, which is consistent with the surface morphology observed by SEM ( Figure 4a, c) in the figure. As for the glassy carbon electrode without guanine molecular imprinting loading in comparative example 2, the preparation process is different from that of the glassy carbon electrode loaded with molecular imprinting, and the only difference is that guanine is not added as a template molecule. Therefore, in terms of surface morphology, compared with the glassy carbon electrode loaded with molecular imprinting, there are no specific holes of guanine molecular imprinting, and only the state of polymer covering the surface is shown, so the surface is smooth with fewer holes, which is consistent with the surface morphology observed by SEM ( Figure 4 b) and d) in the figure are consistent.
[0119] Elemental Analysis of Molecularly Imprinted Glassy Carbon Electrode
[0120] The experiment used XPS to analyze the composition elements of the molecularly imprinted glassy carbon electrode. Figure 5 ) analysis. It can be obtained that the components of the molecularly imprinted glassy carbon electrode are mainly C, O, N, and S. The percentage of the quantified elements is shown in Table 3. By comparing the four elements, it can be obtained that the element content is: C>O>N>S, C is the main component, and the content of N and S is very small.
[0121] Table 3 Element content analysis
[0122]
[0123] Observe the C1s narrow spectrum ( Figure 6 ) The curve is relatively smooth, and the peak appears at the bond energy of 284.80 eV. Through peak fitting, it is found that the C in the molecularly imprinted glassy carbon electrode mainly exists in CC, followed by CO, and C=O is the least. Observe the O1s narrow spectrum ( Figure 7 ), it can be found that the curve is relatively smooth, slightly rough, with a main peak, but the main peak has a certain bifurcation, divided into three small peaks, located at binding energies of 531.28eV, 531.68eV, and 531.88eV, respectively, and the peaks are located at 531.68eV and 531.88eV. After peak fitting, it is found that the main form of O in the molecularly imprinted glassy carbon electrode is C=O, and there is also a small amount of CO. Observe the N1s narrow spectrum ( Figure 8 ) The curve is not smooth and has many spikes, indicating that the N content is low or unevenly distributed, and the content of this element is relatively low within the range of the tested samples. The two peaks are located at 400.38eV and 400.88eV. After peak fitting processing, it is found that the existence form of N is C-NH2. In the process of material preparation, six elements, C, H, O, S, Cl, and N, are mainly involved. In the XPS analysis, there are three elements, C, O, N, and S (XPS cannot detect H element). It is speculated that the reaction is relatively complete during the material synthesis process. There is very little N element, indicating that guanine (C5H5N5O) in the molecularly imprinted glassy carbon electrode is almost completely washed away by hydrochloric acid, leaving the specific molecular imprint of guanine.
[0124] Analysis of extracellular resistance genes by selective electrochemical oxidation degradation on molecularly imprinted glassy carbon electrodes
[0125] The efficiency of electrochemical oxidation degradation of extracellular resistance genes by the optimized molecularly imprinted glassy carbon electrode was compared with that of the glassy carbon electrode without guanine molecular imprinting loading in comparative example 2 and the unmodified glassy carbon electrode (G) in comparative example 3 to study the advantages of the molecularly imprinted glassy carbon electrode in specifically degrading extracellular resistance genes. The results are as follows Fig. 9 . By comparing the curves, it can be found that the three types of glassy carbon electrodes loaded with molecular imprinting as anodes for electrochemical oxidation and degradation of extracellular resistance genes are more effective than the ordinary glassy carbon electrode (G) of Comparative Example 3 and the glassy carbon electrode without guanine molecular imprinting loading of Comparative Example 2. Since the surface of the glassy carbon electrode loaded with molecular imprinting contains guanine molecular imprinting-specific recognition sites, the resistance genes in the electrolyte solution can be increased to move to the anode surface, so that the free radicals generated by the anode can react with the resistance genes to accelerate the removal of the resistance genes. The glassy carbon electrode without guanine molecular imprinting loading of Comparative Example 2 is not as effective in removing resistance genes as the unmodified ordinary glassy carbon electrode (G). This may be because the surface of the glassy carbon electrode without guanine molecular imprinting loading of Comparative Example 2 is wrapped by a large amount of polymers, which relatively reduces the effective surface area of the anode, resulting in a decrease in the electrochemical oxidation effect, and the degradation effect is not as good as that of the unmodified glassy carbon electrode. Specifically, the degradation test results at 30 minutes are shown in Table 4 below:
[0126] Table 4 Effect of different treatments on the degradation of resistance genes
[0127] parameter Degradation rate (%) Comparative Example 1 54.54 Comparative Example 2 66.12 Comparative Example 3 76.06 Comparative Example 4 77.04 Example 1 88.73
[0128] Using the glassy carbon electrodes of Example 1 and Comparative Example 4 that were recovered after the explanation, after secondary degradation, the degradation change rate of Example 1 (the ratio of the difference between the two degradation rate changes to the first degradation rate) was 3-5%, while the degradation change rate of Comparative Example 4 was 45-60%. It can be seen that the molecular imprinting load in Comparative Example 4 is unstable and easy to fall off, while that in Example 1 of the present invention is relatively stable.
[0129] Effect of current density on electrochemical oxidation performance
[0130] This experiment uses a constant current stabilized power supply to supply power. By adjusting the current value (20mA, 40mA, 50mA, 60mA), different current densities (surface area of the glassy carbon electrode loaded with molecular imprinting = 0.942cm 2 The current density is 21.23 mA / cm 2 , 42.46mA / cm 2 , 53.08mA / cm 2 、63.69mA / cm2 ), the experimental results are as follows Fig.10 The results show that increasing the current density can effectively improve the removal rate of extracellular resistance genes, but at a current density of 63.69 mA / cm 2 When compared with 53.08 mA / cm2, the degradation efficiency is not much improved, and the degradation efficiency is not as good as 53.08 mA / cm2 at 30 minutes. 2 The increase of current density can increase the generation of ·OH, etc., but it will lead to the intensification of side reactions under too high current density. Therefore, the energy consumption and removal efficiency are comprehensively analyzed, as shown in Table 5. From the data in Table 5, it can be seen that the current density is 53.08mA / cm 2 When the energy consumption increases, the removal rate of the extracellular resistance genes increases significantly. However, further increasing the current not only increases the energy consumption, but also reduces the removal rate. Therefore, the optimal current density is determined to be 53.08 mA / cm 2 .
[0131] Table 5 Comprehensive analysis of degradation of extracellular resistance genes at different current densities
[0132]
[0133] Effect of electrolyte concentration on electrochemical oxidation performance
[0134] The electrolyte in this experiment is sodium sulfate solution, and different concentrations of sodium sulfate solution are prepared (0.1M, 0.2M, 0.3M, and 0.4M respectively). The experimental results are as follows Fig.11 . Analysis of the experimental results shows that when the electrolyte concentration is low, as the electrolyte concentration increases, the removal rate of extracellular resistance genes also increases accordingly. However, when the electrolyte concentration increases to 0.5M, the resistance gene removal rate decreases instead. The efficiency and energy consumption analysis under different electrolyte concentrations are shown in Table 6. From the data in Table 6, it can be seen that increasing the electrolyte concentration can also reduce the consumption of electrical energy. As the electrolyte concentration increases, the collisions between ions in the reaction system increase, but if the concentration is too high, the electrolyte will be adsorbed on the electrode surface, hindering the migration of pollutants to the electrode surface and reducing the chance of pollutants reacting with reactive groups near the electrode. Taking all factors into consideration, the optimal Na2SO4 concentration is 0.4M.
[0135] Table 6 Comprehensive analysis of the removal rate of extracellular resistance genes under different electrolyte concentrations
[0136] Electrolyte concentration Current (mA) Voltage (V) Energy consumption (kWh) Degradation rate (%) 0.1M 50 5.2 0.94 71.61 0.2M 50 4.1 0.74 75.63 0.3M 50 3.2 0.58 80.05 0.4M 50 2.9 0.52 93.70 0.5M 50 2.7 0.49 80.81
[0137] Selective study of molecularly imprinted glassy carbon electrodes for resistance to gene degradation
[0138] The previous experiments all considered the degradation of extracellular resistance genes under single component conditions. This section mainly studies the selective electrochemical oxidation performance of the molecularly imprinted glassy carbon electrode on extracellular resistance genes in the eARGs+10mg / L humic acid system, eARGs+40mg / L glucose system, and eARGs+20mg / L amino acid system. This experiment was conducted at a current density of 53.08mA / cm 2 The experimental results are shown in Figure 2. Fig.12 As shown. The results show that in the two-component system, the removal efficiency of extracellular resistance genes has decreased slightly, but within the reaction time of 30 minutes, the removal rate can reach more than 60%. When other components are present, the mass transfer of resistance genes is hindered to a certain extent, and they will compete with extracellular resistance genes for free radicals, resulting in a decrease in the removal rate of extracellular resistance genes. When the component is eARGs+10mg / L humic acid, humic acid has little effect on the efficiency of molecularly imprinted glassy carbon electrode in degrading extracellular resistance genes, and still retains 88.90%. Glucose and amino acids have a slightly greater effect on the removal of extracellular resistance genes, but the degradation rates are still retained at 73.31% and 78.31%. Continuing to extend the reaction time can achieve a higher removal rate for extracellular resistance genes. Overall, the molecularly imprinted glassy carbon electrode has the ability to selectively electrochemically oxidize and degrade extracellular resistance genes.
[0139] Reaction kinetics studies
[0140] The kinetic study was conducted under the condition of single component of extracellular resistance gene, and the sampling time points were 0min, 10min, 20min, 30min, 40min and 60min. The Ln(C / C0)-Reactiontime curve was drawn after processing the experimental data, as shown below Fig.13 . Fig.13 It shows that Ln(C / C0) has a good linear relationship with the reaction time, and the reaction process of electrochemical oxidation degradation of extracellular resistance genes by the molecularly imprinted glassy carbon electrode conforms to the first-order kinetic equation, R2=0.97603, and the kinetic equation is c=c0e-0.05691t. The reaction rate constant k=0.05691min-1. By performing first-order kinetic fitting on the ordinary glassy carbon electrode and the glassy carbon electrode of comparative example 2 that is not loaded with guanine molecular imprinting, the rate constants are k1=-0.04749 (R2=0.99714) and k2=-0.03946 (R2=0.99559), respectively. It can be obtained that k>k1>k2, and the molecularly imprinted glassy carbon electrode has the maximum reaction rate. The results of the present invention effectively improve the efficiency of resistance gene removal.
Claims
1. A method for selectively degrading resistance genes in water by electrochemical oxidation, characterized in that: include: Using the first electrode as an anode and the second electrode as a cathode, applying current to degrade the resistance gene in the water body; Wherein, the first electrode is a glassy carbon electrode loaded with molecular imprinting; The molecularly imprinted glassy carbon electrode is obtained by loading the glassy carbon electrode with carbon nanotubes, modifying the ethylene end groups, and loading the molecular imprints. The molecular imprints are used to selectively identify resistance genes from chemical pollutants in water and combine with the resistance genes. The resistance genes are antibiotic resistance genes produced by pathogenic bacteria.
2. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The method for loading carbon nanotubes on a glassy carbon electrode comprises: The glassy carbon electrode is placed in a carboxylated carbon nanotube dispersion, and deposited at a set voltage of -1 to -1.2 V for a deposition time of 1000 to 1300 s to obtain a carbon nanotube-loaded glassy carbon electrode; The carboxylated carbon nanotube dispersion is obtained by dispersing the carboxylated carbon nanotubes in an N,N-dimethylformamide solvent, and the concentration of the carboxylated carbon nanotube dispersion is 0.02-0.05 mg / mL.
3. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 2, characterized in that: The method for modifying the ethylene end groups comprises: S1-1, adding a carbon nanotube-loaded glassy carbon electrode to a mixture of thionyl chloride and tetrahydrofuran to form a suspension, and then reflux the suspension at 50-70° C. for 20-30 hours to obtain a precipitate; S1-2, after washing and drying the precipitate, adding it to tetrahydrofuran, adding 3-butene-1-ol and 4-dimethylaminopyridine, reflux the product at 40-60° C. for 20-30 h, and then centrifuging, washing, and drying to obtain a glassy carbon electrode modified with ethylene end groups; Among them, the addition ratio of glassy carbon electrode, tetrahydrofuran, dichlorothionyl in S1-1 and tetrahydrofuran, 3-butene-1-ol, 4-dimethylaminopyridine in S1-2 is: 10-30g: 300-500ml; 10-20ml: 300-500ml: 10-30ml: 10-30ml.
4. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The second electrode is any one of a platinum electrode, a titanium electrode, a glassy carbon electrode, a BDD electrode and a metal oxide electrode.
5. The method for selectively degrading resistance genes in water by electrochemical oxidation as claimed in claim 3, characterized in that: The method for loading molecular imprinting comprises: S1. Put the glassy carbon electrode modified with ethylene end groups into a mixture of acetonitrile and toluene, add the template molecule guanine and the functional monomer methacrylic acid respectively; stir for 30 minutes and then add the crosslinking agent and initiator; S2, then heating at 70°C for 12h to obtain a product, washing the product with ethanol, hydrochloric acid, and ethanol in sequence, and vacuum drying to obtain a guanine-imprinted glassy carbon electrode; Among them, the added amounts of the glassy carbon electrode after ethylene end group modification, acetonitrile, toluene, template molecule guanine, functional monomer methacrylic acid, cross-linking agent, and initiator are as follows: 10-30 g of glassy carbon electrode after ethylene end group modification, 200-300 mL of acetonitrile, 100-200 mL of toluene, 10 mmol of template molecule guanine, 1-5 mol of functional monomer methacrylic acid, 100-200 mg of cross-linking agent, and 10-40 mg of initiator.
6. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The molecularly imprinted glassy carbon electrode has a diameter of 5 mm and a length of 100 mm.
7. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The current density of the applied current is: 50~60mA / cm 2 .
8. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The degradation time is 10 to 40 minutes.
9. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The chemical pollutants are humic acid and its derivatives, glucose and its derivatives, amino acids and their derivatives.
10. The method for selectively degrading resistance genes in water by electrochemical oxidation according to claim 1, characterized in that: The antibiotic resistance genes include: tetracycline resistance genes, sulfonamide resistance genes, macrolide resistance genes and lactam resistance genes.
Citation Information
Patent Citations
Preparation method of electrode modified by carbon nano-tube
CN101158663A
Molecularly imprinted polymer / carbon nano-tube / basal electrode modified electrode and application thereof
CN101738423A
Carbon nanotube surface molecularly imprinted polymer as well as preparation method and application thereof
CN103965418A
Carbon nanomaterial-based flexible super capacitor electrode material and preparation method for same
CN104201007A
Selective separation of heavy metal ion using the metalion imprinted polymer(MIIP)
KR100723919B1
